MORPHOLOGICAL AND SYNTACTIC PERSPECTIVES ON VERB TENSES: IBN TAYMIYYAH’S CONTRIBUTIONS TO ARABIC GRAMMAR - Gumilar, Rizki (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
The study of verb tenses in the Arabic language has long been a fundamental aspect of Arabic grammar, with traditional classifications focusing on morphological tense. However, the complexity of verb tense interpretation, particularly when considering the influence of context, requires a deeper exploration. Ibn Taymiyyah, a prominent figure in Arabic linguistic thought, offers a unique perspective on verb tenses by categorizing them not only morphologically but also syntactically. This research aimed to explore Ibn Taymiyyah's classification of verb tenses in the Arabic language, focusing on both morphological and syntactic structures. While traditional Arabic grammar generally categorizes verb tenses into past, present, and future based on the verb’s inherent form, Ibn Taymiyyah introduces a more nuanced perspective by emphasizing the role of context in determining verb tense, a concept known as syntactic tense. This study utilized a descriptive-analytical approach to examine Ibn Taymiyyah's works, comparing his views on tense with those of earlier and contemporary Arabic grammarians. The findings reveal that Ibn Taymiyyah aligns with the traditional morphological categorization of tenses but introduces significant differences in how syntactic factors affect the interpretation of tense. Specifically, his understanding of syntactic tense, which is influenced by contextual elements, contrasts with the more rigid, form-based definitions of tense found in earlier grammatical traditions. The study also highlights the unique aspects of Ibn Taymiyyah's theories, such as his interpretation of لا يفعل (lā yaf’alu – he does not do/will do) as negating both present and future, which deviates from the conventional view of negating only the future. The research contributes to Arabic linguistic thought by emphasizing the importance of context in the study of verb tenses and offers new insights into the dynamic relationship between morphology and syntax in Arabic grammar. This work not only deepens our understanding of Ibn Taymiyyah's influence on Arabic linguistics but also provides a foundation for future research in both classical and contemporary linguistic studies.